ChemInform Abstract: Silicon‐Directed Rhenium‐Catalyzed Allylic Substitutions with N‐Hydroxycarbamates, N‐Hydroxysulfonamides, and Hydroxamic Acids. Issue 18 (May 2015) - Chavhan, Sanjay W.; McAdam, Catherine A.; Cook, Matthew J.
Abstract In case of Cbz‐protected hydroxylamine excellent N/O‐selectivities up to 99:1 are observed.